The use of sonicated lipid vesicles for mass spectrometry of membrane protein complexes - Chorev, DS; Tang, H; Rouse, SL; Bolla, JR; von Kügelgen, A; Baker, LA; Wu, D; Gault, J; Grünewald, K; Bharat, TAM; Matthews, SJ; Robinson, CV (Nature Research, 2020)
Recent applications of mass spectrometry (MS) to study membrane protein complexes are yielding valuable insights into the binding of lipids and their structural and functional roles. To date, most native MS experiments with membrane proteins are based on detergent solubilization. Many insights into the structure and function of membrane proteins have been obtained using detergents; however, these can promote local lipid rearrangement and can cause fluctuations in the oligomeric state of protein complexes. To overcome these problems, we developed a method that does not use detergents or other chemicals. Here we report a detailed protocol that enables direct ejection of protein complexes from membranes for analysis by native MS. Briefly, lipid vesicles are prepared directly from membranes of different sources and subjected to sonication pulses. The resulting destabilized vesicles are concentrated, introduced into a mass spectrometer and ionized. The mass of the observed protein complexes is determined and this information, in conjunction with ‘omics’-based strategies, is used to determine subunit stoichiometry as well as cofactor and lipid binding. Within this protocol, we expand the applications of the method to include peripheral membrane proteins of the S-layer and amyloid protein export machineries overexpressed in membranes from which the most abundant components have been removed. The described experimental procedure takes approximately 3 d from preparation to MS. The time required for data analysis depends on the complexity of the protein assemblies embedded in the membrane under investigation.